Quality Improvement Initiative Reduces the Occurrence of Complications in Peripherally Inserted Central Catheters. Issue 1 (January 2019) - Walters, Beth; Price, Chelsey
Abstract : Peripherally inserted central catheters (PICCs) are commonly used to access the central venous system. However, central vascular access devices are associated with a risk of complications, which may include infection, thrombosis, occlusion, or malposition. The vascular access team of 1 midwestern hospital used a quality improvement initiative to reduce the occurrence of complications associated with PICCs. A secondary aim was to reduce the number of alteplase (Cathflo Activase; Genentech, South San Francisco, CA) doses administered. After reviewing current evidence, the vascular access team employed the Plan-Do-Study-Act cycle to document and implement changes in practice. By using a team initiative to investigate this issue, complication rates decreased and patient satisfaction improved. The thrombosis rate decreased by 67%, occlusions by 75%, and alteplase use by 87%. No infections occurred during this study.